Factors Affecting Audit Quality (Survey at Public Accounting Firms in Bandung and Jakarta) - et. al., Rini Susiani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study is to determine the factors that affect the quality of the audit. The sampling technique used is convenience sampling, with the Public Accounting Firm's unit of analysis, the respondents were auditors who served in the Public Accounting Firm (KAP) in Bandung and Jakarta, and obtained a sample of 39 respondents from 12 public accounting firms. The analytical method used is multiple regression analysis at a significance level of 5% with an analysis tool using SPSS 25, which shows the partial results of Time Budget Pressure and Quality Control System affect Audit Quality and both of these variables simultaneously have an effect on Audit Quality